Moyamoya Disease Involving Anterior and Posterior Circulation in Pediatric Ischemic Stroke: Rare Case Report - Subandi Subandi; Lothar Matheus Manson Vanende Silalahi (Journal of Neurointervention and Stroke, 2025)
Highlight: Moyamoya disease is one of the causes of stroke in children Moyamoya disease typically involves anterior circulation Posterior circulation may also be involved in certain cases of Moyamoya disease ABSTRACT Introduction: Ischemic stroke is frequently observed in adults but may also occur in children. Moyamoya disease (MMD) is one of the causes of ischemic stroke in children. MMD is a progressive steno-occlusive large-vessel cerebral arteriopathy. MMD was initially defined as changes in the carotid artery with an abnormal vascular network, however, the changes were also noted in posterior circulation. Case: We reported the case of a 13-year-old male with right-sided weakness persisting for over 3 years. Magnetic resonance imaging revealed cortical infarction in the left parietal lobe. Digital subtraction angiography (DSA) confirmed moyamoya disease by revealing total occlusion of the bilateral terminal internal carotid artery and bilateral posterior cerebral artery, accompanied  by a puff of smoke appearance. We treated this patient with antiplatelet therapy for secondary stroke prevention. Conclusion: MMD is one of the conditions that can cause ischemic stroke in children. The posterior circulation is another possible site of MMD manifestation, but it is mostly found in cerebral anterior circulation.